2009
DOI: 10.1161/hypertensionaha.109.131391
|View full text |Cite
|
Sign up to set email alerts
|

Chymase Plays an Important Role in Left Ventricular Remodeling Induced by Intermittent Hypoxia in Mice

Abstract: Abstract-Intermittent hypoxia caused by sleep apnea is associated with cardiovascular disease. Chymase has been reported to play an important role in the development of cardiovascular disease, but it is unclear whether chymase is involved in the pathogenesis of left ventricular remodeling induced by intermittent hypoxia. The aim of this study was to evaluate the effect of a novel chymase inhibitor (NK3201) on hypoxia-induced left ventricular remodeling in mice. Male C57BL/6J mice (9 weeks old) were exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 53 publications
(53 reference statements)
1
29
0
Order By: Relevance
“…Chymase inhibitors are also effective in models for myocardial infarction, 102,103 intimal hyperplasia after balloon injury, 104 Big endothelin-1 conversion, 105 and ventricular remodeling induced by intermittent hypoxia. 106 In addition, chymase inhibitors have anti-inflammatory functions, for example, by reducing the eosinophilia during N brasiliensis infection 107 and by preventing eosinophil accumulation in a model for atopic dermatitis. 108 Together, this development strongly implicates chymase as a promising therapeutic target in variety of clinical settings, and we anticipate that this notion will be evaluated through clinical trials in the near future.…”
Section: Chymase Inhibitorsmentioning
confidence: 99%
“…Chymase inhibitors are also effective in models for myocardial infarction, 102,103 intimal hyperplasia after balloon injury, 104 Big endothelin-1 conversion, 105 and ventricular remodeling induced by intermittent hypoxia. 106 In addition, chymase inhibitors have anti-inflammatory functions, for example, by reducing the eosinophilia during N brasiliensis infection 107 and by preventing eosinophil accumulation in a model for atopic dermatitis. 108 Together, this development strongly implicates chymase as a promising therapeutic target in variety of clinical settings, and we anticipate that this notion will be evaluated through clinical trials in the near future.…”
Section: Chymase Inhibitorsmentioning
confidence: 99%
“…The fibrotic area in the cardiac tissues and the mRNA levels of collagen I and collagen III were also significantly lower in the chymase inhibitor-treated group. Recently, we also demonstrated that cardiac fibrotic areas under intermittent hypoxia were also significantly attenuated by treatment with a chymase inhibitor in rats (57). Therefore, the pathway forming chymase-dependent TGF-Ī² may play an important role in myocardial fibrosis and cardiac dysfunction after myocardial infarction.…”
Section: Cardiac Dysfunction and Fibrosismentioning
confidence: 88%
“…The deleterious effect of unopposed Chymase activity was associated with poor clinical outcome [32]. In a pre-clinical study, Chymase was able to induce hypoxia in myocardium leading to remodeling of cardiac architecture independent of blood pressure [33] although this has not been firmly established in humans. Acute myocardial infarction resulting from sudden occlusion of the coronary artery is dependent on sudden rupture of the atheroma cap.…”
Section: Distribution and Activity Of Chymase In Cardiac Tissuementioning
confidence: 99%